Physician-staffed helicopter emergency medical services augment ground ambulance paediatric airway management in urban areas: a retrospective cohort study. Issue 11 (3rd October 2019) - Garner, Alan A; Bennett, Nicholas; Weatherall, Andrew; Lee, Anna
Abstract : Objectives: Paediatric intubation is a high-risk procedure for ground emergency medical services (GEMS). Physician-staffed helicopter EMS (PS-HEMS) may bring additional skills, drugs and equipment to the scene including advanced airway management beyond the scope of GEMS even in urban areas with short transport times. This study aimed to evaluate prehospital paediatric intubation performed by a PS-HEMS when dispatched to assist GEMS in a large urban area and examine how often PS-HEMS provided airway intervention that was not or could not be provided by GEMS. Methods: We performed a retrospective observational study from July 2011 to December 2016 of a PS-HEMS in a large urban area (Sydney, Australia), which responds in parallel to GEMS. GEMS intubate without adjuvant neuromuscular blockade, whereas the PS-HEMS use neuromuscular blockade and anaesthetic agents. We examined endotracheal intubation success rate, first-look success rate and complications for the PS-HEMS and contrasted this with the advanced airway interventions provided by GEMS prior to PS-HEMS arrival. Results: Overall intubation success rate was 62/62 (100%) and first-look success was 59/62 (95%) in the PS-HEMS-treated group, whereas the overall success rate was 2/7 (29%) for the GEMS group. Peri-intubation hypoxia was documented in 5/65 (8%) of the PS-HEMS intubation attempts but no other complications were reported. However, 3/7 (43%) of the attempted intubations by GEMS were oesophageal intubations, two of which were unrecognised. Conclusions: PS-HEMS have high success with low complication rates in paediatric prehospital intubation. Even in urban areas with rapid GEMS response, PS-HEMS activated in parallel can provide safe and timely advanced prehospital airway management for seriously ill and injured children beyond the scope of GEMS practice. Review of GEMS airway management protocols and the PS-HEMS case identification and dispatch system in Sydney is warranted.